Nonhealing Ulcer: Acroangiodermatitis of Mali - Neeraj Varyani; Anubhav Thukral; Nilesh Kumar; Kailash Kumar Gupta; Ravi Tandon; Kamlakar Tripathi (Case Reports in Dermatological Medicine)
An 18-year-old male presented with a nonhealing wound on left lower limb, pain and swelling over multiple joints, weight loss, and yellowish discoloration of eyes and urine for the past 4 years. On examination, the patient had pallor, icterus, and generalized lymphadenopathy with a nonhealing unhealthy ulcer over left medial malleolus. He had deformed joints with hepatomegaly and splenomegaly. His laboratory investigations were positive for antinuclear antibody (ANA) and anticardiolipin antibody (ACLA). Synovial fluid analysis showed inflammatory findings. Biopsy of margin of the ulcer showed findings consistent with Acroangiodermatitis of Mali. The patient was treated with disease-modifying antirheumatic drugs (DMARDs) and aspirin for juvenile idiopathic arthritis and secondary antiphospholipid antibody syndrome (APS), respectively. The ulcer was managed conservatively with systemic antibiotics and topical steroids along with limb elevation and compression elastic stockings. The patient's symptoms improved significantly, and he is in our followup.